2016
DOI: 10.31018/jans.v8i2.878
|View full text |Cite
|
Sign up to set email alerts
|

Economic feasibility of summer squash cultivation using low tunnel and black plastic mulch under tarai condition of Uttarakhand

Abstract: A study was undertaken to investigate the economic feasibility of summer squash cultivation in tarai region of Uttarakhand during winter - spring season of 2013-14 and 2014-15. Among three transplanting dates, summer squash transplanted on 15th January was found to be best with respect to plant growth characters, total yield (373.50 q ha-1), net return (`2,46,542 ha-1) and benefit – cost ratio (2.72). Similarly, out of three low cost protected techniques evaluated along with control, low tunnel with black pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Ansary and Roy [22] observed higher yield of watermelon in mulched treatment as compared to control, due to higher vegetative growth under mulches. Similar results were also recorded by Bhatt et al [13], Singh et al [14] and Thapliyal et al [17] in summer squash; Hedau and Kumar [23] and Singh et al [24] in tomato; Singh et al [16] in bitter gourd; Awasthi et al [20] in brinjal; and Nimah [25] in cucumber.…”
Section: Fruit and Yield-related Attributessupporting
confidence: 85%
See 1 more Smart Citation
“…Ansary and Roy [22] observed higher yield of watermelon in mulched treatment as compared to control, due to higher vegetative growth under mulches. Similar results were also recorded by Bhatt et al [13], Singh et al [14] and Thapliyal et al [17] in summer squash; Hedau and Kumar [23] and Singh et al [24] in tomato; Singh et al [16] in bitter gourd; Awasthi et al [20] in brinjal; and Nimah [25] in cucumber.…”
Section: Fruit and Yield-related Attributessupporting
confidence: 85%
“…and development of the plants. Similar findings of better growth of summer squash by the use of plastic mulch were also reported by Bhatt et al [13] and Singh et al [14]. Higher soil temperature under black plastic mulch improved the plant microclimate, leading to early growth and development [15].…”
Section: Galley Proofsupporting
confidence: 82%
“…According to reports, black plastic mulch films are more effective than white, aluminum/black plastic mulch films in boosting minimum, maximum, and mean soil temperature (Claudio et al, 2017). Many crops yielded more under black-colored mulch films than in bare fields (Rashidi et al, 2010;Berihun 2011;Bhatt et al, 2011;Hatami et al, 2012;Kumar and Lal 2012). The effects of black polyethylene plastic mulch on okra and squash growth and yield under rain-fed conditions revealed that plants with polyethylene mulch produce larger fruits and higher fruit yield per plant.…”
Section: Black Coloured Plastic Mulch Filmmentioning
confidence: 99%